A Phase Ia/b study of MEK1/2 inhibitor binimetinib with MET inhibitor crizotinib in patients with RAS mutant advanced colorectal cancer (MErCuRIC) - Francesca Aroldi; Elena Elez; Thierry André; Geraldine Perkins; Hans Prenen; Vlad Popovici; Peter Gallagher; Jennifer Houlden; Linda Collins; Corran Roberts; Christian Rolfo; Federica Di Nicolantonio; et al. (BMC Cancer)
Abstract Background Targeting RAS mutant (MT) colorectal cancer (CRC) remains a difficult challenge, mainly due to the pervasiveness of RAS/MEK-mediated feedback loops. Preclinical studies identified MET/STAT3 as an important mediator of resistance to KRAS-MEK1/2 blockade in RASMT CRC. This dose escalation/expansion study assessed safety and initial efficacy of the MEK1/2 inhibitor binimetinib with MET inhibitor crizotinib in RASMT advanced CRC patients. Methods In the dose escalation phase, patients with advanced solid tumours received binimetinib with crizotinib, using a rolling- 6 design to determine the maximum tolerable dose (MTD) and safety/tolerability. A subsequent dose expansion in RASMT CRC patients assessed treatment response. Blood samples for pharmacokinetics, MET biomarker and ctDNA analyses, and skin/tumour biopsies for pharmacodynamics, c-MET immunohistochemistry (IHC), MET in situ hybridisation (ISH) and MET DNA-ISH analyses were collected. Results Twenty patients were recruited in 3 cohorts in the dose escalation. The MTD was binimetinib 30 mg B.D, days 1–21 every 28 days, with crizotinib 250 mg O.D continuously. Dose-limiting toxicities included grade ≥ 3 transaminitis, creatinine phosphokinase increases and fatigue. Thirty-six RASMT metastatic CRC patients were enrolled in the dose expansion. Pharmacokinetic and pharmacodynamic parameters showed evidence of target engagement. Across the entire study, the most frequent treatment-related adverse events (TR-AE) were rash (80.4%), fatigue (53.4%) and diarrhoea (51.8%) with grade ≥ 3 TR-AE occurring in 44.6%. Best clinical response within the RASMT CRC cohort was stable disease in seven patients (24%). Tumour MET super-expression (IHC H-score > 180 and MET ISH + 3) was observed in 7 patients (24.1%), with MET-amplification only present in 1 of these patients. This patient discontinued treatment early during cycle 1 due to toxicity. Patients with high baseline RASMT allele frequency had a significant shorter median overall survival compared with that seen for patients with low baseline KRASMT allele frequency. Conclusions Combination binimetinib/crizotinib showed a poor tolerability with no objective responses observed in RASMT advanced CRC patients. EudraCT-Number: 2014–000463 - 40 (20/06/2014: A Sequential Phase I study of MEK1/2 inhibitors PD- 0325901 or Binimetinib combined with cMET inhibitor Crizotinib in RAS Mutant and RAS Wild Type with aberrant c-MET).